2014
DOI: 10.1089/vbz.2014.1596
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Batai Virus Infections, Bovines, Northern Italy, 2011

Abstract: Batai virus (BATV) was identified in mosquitoes in the Caltignaga region of Novarra, northern Italy in 2009. Here, we report the identification of antibodies to BATV in serum samples that were taken from healthy bovines in that region in 2011. BATV has been associated with a mild febrile human illness and identified as the likely parental segment donor in a reassortment event that resulted in the generation of the virulent progeny, Ngari virus. The possible veterinary disease associations of BATV are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…This is in line with a recent study from northern Italy that demonstrated serological evidence (by IIFA and VNT) of BATV infections in cattle from an area with previous evidence of BATV circulation in mosquitoes (9,10). However, the observed BATV seroprevalence in cattle from northern Italy was significantly higher (7%) than the BATV seroprevalence in southwest Germany (9). In addition, our study highlighted the advantage of using two different assays (IB and IIFA) in parallel.…”
supporting
confidence: 92%
“…This is in line with a recent study from northern Italy that demonstrated serological evidence (by IIFA and VNT) of BATV infections in cattle from an area with previous evidence of BATV circulation in mosquitoes (9,10). However, the observed BATV seroprevalence in cattle from northern Italy was significantly higher (7%) than the BATV seroprevalence in southwest Germany (9). In addition, our study highlighted the advantage of using two different assays (IB and IIFA) in parallel.…”
supporting
confidence: 92%
“…In other European countries (Finland, Austria, Slovakia, Portugal, Romania, and former Yugoslavia) antibody titers detected by HI ranged from 1% to 46% in cattle and sheep [17]. A recent study in northern Italy found nine antibody-positive cattle out of 128 tested animals, corresponding to a prevalence of 7% [18]. In humans, the prevalence of HI antibodies was generally very low (<1%) in Sweden, Finland, Germany, Austria, and former Yugoslavia, but reached 32% in southern Slovakia [17].…”
Section: Discussionmentioning
confidence: 99%
“…To date, serological investigations for BATV have been conducted by hemagglutination inhibition tests (HI), SNTs, plaque reduction neutralization tests (PRNTs), and by immunofluorescence assays (IFAs). As these sensitive tests depend on the prior cultivation of live virus, they require higher biosafety standards [9,[16][17][18]. Therefore, we implemented an indirect ELISA based on the partial recombinant BATV glycoprotein Gc for To date, serological investigations for BATV have been conducted by hemagglutination inhibition tests (HI), SNTs, plaque reduction neutralization tests (PRNTs), and by immunofluorescence assays (IFAs).…”
Section: Discussionmentioning
confidence: 99%
“…This virus is an orthobunyavirus with a reassortant between Bunyamwera virus and an M segment donated from Batai virus [9][10][11]. Of interest, Batai virus, the starting donor virus of the new Ngari virus, can cause a mild febrile human illness [12]. However, when the reassorement occurs, the resulted virus is highly virulent [12].…”
Section: Ngari Virusmentioning
confidence: 99%
“…Of interest, Batai virus, the starting donor virus of the new Ngari virus, can cause a mild febrile human illness [12]. However, when the reassorement occurs, the resulted virus is highly virulent [12]. Tracking for the viral origin, it is mentioned that the development of virus occurs in Sudan and Uganda.…”
Section: Ngari Virusmentioning
confidence: 99%